How Much Does Social Status Matter to Health? Evidence from China's Academician Election - Gordon G. Liu; Ohyun Kwon; Xindong Xue; Belton M. Fleisher (Institute for the Study of Labor (IZA), 2014)
The impact of socio-economic status on health has been widely recognized, but the independent impact of social status alone on health remains inconclusive. We approach this challenge by exploiting a natural experiment in which subjects undergo a shift in their social status without considerable economic impact. We gather data on 4190 scientists who were either nominated for or successfully elected to the Chinese Academy of Science or of Engineering. Being elected as an academician in China is a boost in social status (vice-ministerial level) with negligible economic impact (US30 monthly before 2009). After correcting for two sources of bias: 1) Some potential academicians decease too young to be elected, leading to immortal-time bias in favor of academicians and 2) the endogenous relationship between health and social status, we find that the enhanced social status of becoming an academician leads to approximately 1.2-years longer life.
Keywords: I12; 330; social status; health; academician; China